Synthesis of α‐Quaternary β‐Lactams via Copper‐Catalyzed Enantioconvergent Radical C(sp3)−C(sp2) Cross‐Coupling with Organoboronate Esters - Wang, Fu‐Li; Liu, Lin; Yang, Chang‐Jiang; Luan, Cheng; Yang, Jing; Chen, Ji‐Jun; Gu, Qiang‐Shuai; Li, Zhong‐Liang; Liu, Xin‐Yuan (Angewandte Chemie International Edition, 2023)
The copper‐catalyzed enantioconvergent radical C(sp3)−C(sp2) cross‐coupling of tertiary α‐bromo‐β‐lactams with organoboronate esters could provide the synthetically valuable α‐quaternary β‐lactams. The challenge arises mainly from the construction of sterically congested quaternary stereocenters between the tertiary alkyl radicals and chiral copper(II) species. Herein, we describe our success in achieving such transformations through the utilization of a copper/hemilabile N,N,N‐ligand catalyst to forge the sterically congested chiral C(sp3)−C(sp2) bond via a single‐electron reduction/transmetalation/bond formation catalytic cycle. The synthetic potential of this approach is shown in the straightforward conversion of the corresponding products into many valuable building blocks. We hope that the developed catalytic cycle would open up new vistas for more enantioconvergent cross‐coupling reactions. Copper‐catalyzed enantioconvergent radical C(sp3)−C(sp2) cross‐coupling of tertiary alkyl bromides with organoboronate esters is developed to access synthetically valuable α‐quaternary chiral β‐lactams. The success of this work relies on the utilization of chiral N,N,N‐ligands to forge the sterically congested C(sp3)−C(sp2) bonds.